Research and engineering practice of coupled unloading and supporting technology for rock burst prevention in hard coal seams of the Ordos region - Gang, Han; Lin-Ming, Dou; Jia-Hao, Xie; Qian, Zhao; Ya-Wu, Shao; Ming-Ming, Sun; Liang, Mou (Frontiers in Earth Science, 2025)
Hard coal seams in the Ordos region are key geological factors contributing to rock bursts. To overcome the limitations of conventional drilling pressure-relief techniques—such as insufficient unloading efficiency, reliance on high-density multi-round drilling, and support failure—this study establishes a non-isobaric stress field model and analyzes the influence of coal seam strength and drilling diameter on the radius of the drilling-induced plastic zone. Based on this analysis, a coupled “shallow support and deep pressure relief” unloading-support technology was proposed. A 70-m on-site comparative industrial test was conducted using coal-powder monitoring, coal-cannon monitoring, stress monitoring, and surrounding-rock deformation monitoring to evaluate pressure-relief and support performance. The results show that the plastic zone radius is mainly controlled by coal strength and borehole diameter, with diminishing benefits when enlarging the diameter beyond a threshold. The enhanced pressure-relief zone produced 3.1 times more coal powder than traditional drilling, and coal-cannon events concentrated in the 7–14 m range effectively released accumulated elastic energy. Post-relief stress peaks were significantly reduced and recovered more slowly. In terms of roadway stability, anchor-cable stress remained lower and more stable than under conventional drilling, with roadway side convergence and roof–floor convergence reduced by 63% and 51%, respectively. A comprehensive mechanical drilling–based anti-burst technology and equipment system was developed and successfully applied in engineering practice. These findings provide theoretical support and practical guidance for pressure relief and support strategies in hard coal seams of the Ordos region and similar mining conditions.